Albumin-coated pH-responsive dimeric prodrug-based nano-assemblies with high biofilm eradication capacity. (22nd December 2022) - Li, Xueling; Li, Wenting; Li, Keke; Chen, Xiangjun; Wang, Changrong; Qiao, Mingxi; Hong, Wei
Abstract : Schematic illustration of albumin-coated pH-responsive dimeric prodrug-based nano-assemblies for efficient Pseudomonas aeruginosa (PA) biofilms eradication. Abstract : Pseudomonas aeruginosa (PA) biofilms cause many persistent chronic infections in humans, especially in cystic fibrosis (CF) patients. The biofilms form a strong barrier which may inhibit antimicrobial agents from penetrating the biofilms and killing PA bacteria that reside deep within the biofilms. Concomitant therapies based on tobramycin (TOB) and azithromycin (AZM) have demonstrated beneficial effects in CF patients with chronic PA infections. However, the co-delivery of TOB and AZM has rarely been reported. In this study, we constructed a self-assembled pH-sensitive nano-assembly (DPNA) based on a dimeric prodrug (AZM-Cit-TOB) by simply inserting citraconic amide bonds between AZM and TOB. Moreover, the cationic surface of DPNA was further modified with anionic albumin (HSA) via electrostatic interactions to form an electrostatic complex (termed HSA@DPNA) for better biocompatibility. Upon arrival at the infected tissues, the citraconic amide bonds would be cleaved at acidic pH, resulting in the release of TOB and AZM for bacteria killing and biofilm eradication. As expected, HSA@DPNA showed comparable antibacterial abilities against the P. aeruginosa strain PAO1 in both planktonic and biofilm modes of growth compared to the TOB/AZM mixture in vitro . Moreover, HSA@DPNA exhibited excellent therapeutic efficacy on mice with PAO1-induced lung infection compared to the TOB/AZM mixture, and no detectable toxicity to mammalian cells/animals was observed during the therapeutic process. In summary, our study provides a promising method for the co-delivery of AZM and TOB in concomitant therapies against PAO1-related infection.